“Have You Ever Seen Zelensky Without a Haircut?”: Quarantine in Ukraine: The State and the People - Tkhorzhevska, Tetiana; Yakymynska, Liubov; Salamatina, Olga (Anthropologica)

(untitled) (University of Victoria, 2021)
An anthropological study of the state requires an understanding of everyday practices in human-state interaction. This study, which came about when state-imposed pandemic restrictions required that citizens go into quarantine, draws primarily from auto-ethnography. The conditions under a quarantine brought an end to well-established social practices, presenting a unique opportunity to study them. We explore the ways in which citizens construct the state, looking at citizens working in different institutions and attempting to access various services. This is done by evaluating the quarantine measures implemented by the state in an attempt to understand them.